Fiber Design and Fabrication of Yb/Ce Codoped Aluminosilicate Laser Fiber With High Laser Stability - Yuwei Li; Shuang Liu; Huan Zhan; Kun Peng; Shihao Sun; Jiali Jiang; Xiaolong Wang; Li Ni; Lei Jiang; Jianjun Wang; Feng Jing; Aoxiang Lin (IEEE Photonics Journal)
By a chelate precursor doping technique, we designed and fabricated an ytterbium/cerium codoped aluminosilicate fiber for noticeable suppression of photodarkening and demonstrated its laser performance. Cerium/ytterbium ions ratio of 0.5 was specially designed to mitigate photodarkening. Aluminum/fluorine ions ratio of 1 was devised to keep low numerical aperture of fiber core. The measurements showed the fiber core was homogeneously doped with ∼0.12 mol% Yb2O3, ∼0.05 mol% Ce2O3, ∼0.5 mol% Al2O3, and ∼0.2 mol% SiF4, respectively. Tested in a master oscillator power amplifier system, the fiber presented 1930 W laser output power with optical-to-optical efficiency of 79.2%. Stabilized at 1850 W for over 500 min, the output power presented a relatively small power degradation of <1.04%, directly justifying a strong photodarkening resistance. These results demonstrated that ytterbium/cerium codoped aluminosilicate fiber with appropriate concentration ratios of dopants could be an ideal choice for 2 kW-level commercial high power laser applications.